Sources of Resistance to Fusarium solani and Associated Genomic Regions in Common Bean Diversity Panels - Zitnick-Anderson, Kimberly; Oladzadabbasabadi, Atena; Jain, Shalu; Modderman, Chryseis; Osorno, Juan M.; McClean, Phillip E.; Pasche, Julie S. (Frontiers in Genetics, 2020)
Common bean (Phaseolus vulgaris L.) production worldwide is hampered by Fusarium root rot (FRR), which is caused by Fusarium solani. Screening for FRR resistance on a large scale is notoriously difficult and often yields inconsistent results due to variability within the environment and pathogen biology. A greenhouse screening assay was developed incorporating multiple isolates of F. solani to improve assay reproducibility. The Andean (ADP; n = 270) and Middle American (MDP; n = 280) Diversity Panels were screened in the greenhouse to identify genetic factors associated with FRR resistance. Forty-seven MDP and 34 ADP lines from multiple market classes were identified as resistant to FRR. Greenhouse phenotyping repeatability was confirmed via five control lines. Genome-wide association mapping using ∼200k SNPs was performed on standard phenotyping score 1–9, as well as binary and polynomial transformation of score data. Sixteen and seven significant genomic regions were identified for ADP and MDP, respectively, using all three classes of phenotypic data. Most candidate genes were associated with plant immune/defense mechanisms. For the ADP population, ortholog of glucan synthase-like enzyme, senescence-associated genes, and NAC domain protein, associated with peak genomic region Pv08:0.04–0.18 Mbp, were the most significant candidate genes. For the MDP population, the peak SNPs Pv07:15.29 Mbp and Pv01:51 Mbp mapped within gene models associated with ethylene response factor 1 and MAC/Perforin domain-containing gene respectively. The research provides a basis for bean improvement through the use of resistant genotypes and genomic regions for more durable root rot resistance.